Evaluation of effectiveness of an innovative semen extender (Formula®) comparing with a traditional extender (Lepus®) for artificial insemination in rabbits does. Issue 4 (1st October 2016) - Bresciani, Carla; Bianchera, Annalisa; Mazzanti, Pier Marco; Bertocchi, Mara; Bettini, Ruggero; De Cesaris, Valeria; Bigliardi, Enrico; Di Ianni, Francesco; Sabbioni, Alberto; Parmigiani, Enrico
Abstract: This study aimed to investigate the preservability and viability of the rabbit spermatozoa diluted in a new semen extender Formula ® in comparison with Lepus ® at 17 °C of storage. The main characteristic of the new extender formulation is the use of an enzymatic agent associated to a polysaccharide as energy source precursor, added with gentamycin. During eight trials, ejaculates from 70 bucks were collected and diluted at 1:10 ratio with both the extenders, after 24 h of storage the semen doses were used for the artificial insemination (AI). Aliquots of the semen doses for each trial were stored at 17 °C, the total and progressive motility were checked at 0, 4, 12, 18, 24, 36, 48, 60, 72, 84, 96, 108 h of storage. A total of 1267 and 1525 does were inseminated, respectively with Formula ® and Lepus ® . During storage the mean total and progressive motility (77.23% and 72.854%, respectively) were significantly higher for Formula ® ( p < .01) and the progressive motility at almost 70% was maintained for at least 60 h vs the 24 h of storage for Lepus ® with significant differences after 12 h of storage ( p < .05). The new extender reported a higher pregnancy rate ( p < .05) and an average of 9.25 rabbits born per litter vs 8.83 for the traditional extender ( p < .05), while the mean of the newborn alive was 9.08 using Formula ® vs 8.51 with Lepus ® ( p < .05). In conclusion, the use of Formula ® is recommended for rabbit semen AI programmes.